Self‐Assembled Ultrathin Anatase TiO2 Nanosheets with Reactive (001) Facets for Highly Enhanced Reversible Li Storage. Issue 3 (7th October 2013) - Nguyen, Loc H.; Aravindan, Vanchiappan; Kulkarni, Sneha A.; Yanan, Fang; Prabhakar, Rajiv Ramanujam; Batabyal, Sudip K.; Madhavi, Srinivasan
<x xml:space="preserve">Abstract</x> Highly reversible Li storage is achieved using self‐assembled anatase phase TiO2 nanosheets with exposed (001) facets. The obtained devices exhibit excellent cyclability during high‐current operation.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>